Curvularia lunata-Induced Onychomycosis in an Unlikely Host: A Case Report - Marwa Hallal; Grace Obeid (Case Reports in Dermatology)
Introduction: Onychomycosis, a fungal infection of the nail apparatus, presents with various manifestations, including subungual hyperkeratosis, onycholysis, and nail plate destruction. Established risk factors include trauma, advanced age, and comorbidities such as diabetes and immunosuppression. Trichophyton rubrum, classified as a dermatophyte, is the primary causative agent, with dermatophytes contributing to 60–70% of cases. Nondermatophyte molds (NDM) account for 30–40% of onychomycosis with Candida species being the most commonly identified, while Curvularia species are rarely encountered. Curvularia lunata, a saprobic dematiaceous mold, is an infrequent human pathogen primarily residing in soil. While human diseases caused by Curvularia are rare, they encompass a spectrum from skin infections to endocarditis. Case Presentation: This case report details a 53-year-old male engineer presenting with left big toenail discoloration, revealing a C. lunata-induced onychomycosis through positive KOH preparation and culture. Given the patient’s concurrent use of ticagrelor, oral terbinafine hydrochloride was chosen as a therapeutic option, taking into account potential drug-drug interactions. This approach resulted in complete resolution. The discussion emphasizes distinctions in disease severity among immunocompromised and immunocompetent patients, the potential role of trauma in Curvularia infections, and the importance of comprehensive diagnostic examinations. Conclusion: This case report provides insight into the challenges of accurate diagnosis, emphasizing the need for routine fungal cultures. Additionally, it discusses the complexities of treatment options, considering factors such as drug interactions and patient-specific conditions, and highlighting the importance of tailored management plans. This case is reported because of the rarity of onychomycosis caused by Curvularia in immunocompetent individuals.